Alternative method of ventilation air purification during manufacture of cores in cold rigging by purging with amines - Yu. P. Shapovalov; S. S. Deshits; A. S. Galibus (Литьë и металлургия)
А brief description of the technology of an adsorptionbiochemical installation for purification of ventilation air from triethylamine and accompanying substances is given.